Sensitization in the management of solid waste to neighboring from FONAVI and ENACE , in the city of Puerto Maldonado, Madre de Dios region - Mamani, Lucy (2014)
The sensitization study population and production evaluation of PET was performed from January to March 2010 in the city of Puerto Maldonado in the areas of FONAVI and ENACE, both are inhabited by people of lower-middle stratum. Beneficiaries were selected and evaluated prior knowledge about the concepts of segregating, organic and inorganic waste through the use of surveys at the beginning and end of the project. I give them a red bag for separating plastic bottles, which were collected on weekends for storage and weighing. Concepts raised FONAVI neighbors learned more about the concept of segregating but not increase the number of people who knew about organic and inorganic waste. On the other hand, neighbors ENACE who knew the word segregation decreased by 1% probably because they were more concerned in learning the concepts of organic and inorganic waste as initially I was recording 62% of residents who knew the concept, then increased to 77 %. Regarding the PET not I collect the expected amount due to natural phenomena, miners’ strike, mechanical drive pickup.